Utilization of coal burning waste fly ash as a soil improving material in red yellow podsolic soil - Asia Afriyani; Ali Martinus; Inneke Fratiwi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
This research aimed to characterize and test the chemical properties of red-yellow podzolic soil and fly ash. The experiment was conducted using polybags with various dosage levels of 2 types of red-yellow podzolic soil, as well as fly ash. Dolomite was used as a control. The experiment used 3 types of experiments with 3 repetitions on the soil (A1=10 g of fly ash /polybag, A2=15 g of fly ash/polybag, A3=20 g of fly ash/polybag, and A0=10 g of dolomite/polybag as a control). The results showed that the application of fly ash waste can increase the pH of podzolic soil. There was an increase in K-dd from 0.34 to 1.36. Al-dd analysis of the addition of fly ash ameliorant Al-dd levels decreased quite significantly with an average of 5.26‒7.16. Al-dd levels were very low in treatment A3 with the addition of 20 g/polybag. H-dd analysis on Red and Yellow Podzolic soils resulted in an increase in the initial H-dd of the soil from 0.4 to 4.61‒7.16. The highest H-dd was in A2 with the addition of 15 g of fly ash/polybag and the lowest H-dd iss in treatment A3 with the addition of 20 g/polybag.